Electrocatalytic sulfathiazole degradation by a novel nickel-foam cathode coated with nitrogen-doped porous carbon. (20th February 2019) - Deng, Fengxia; Qiu, Shan; Olvera-vargas, Hugo; Zhu, Yingshi; Gao, Weijie; Yang, Jixian; Ma, Fang
Abstract: A new nickel-foam (Ni-F) based cathode was elaborated by coating nitrogen-doped porous carbon (CN/Ni-F) and applied to the electro-Fenton (EF) treatment of sulfathiazole (STZ, a target pollutant). Both Fourier transform infrared spectra (FITR) and X-ray photoelectron spectroscopy (XPS) results confirmed the abundant presence of surface oxygen/nitrogen-containing functional groups after nitrogen-doped porous carbon (CN) introduction. Linear sweep voltammetry (LSV) showed an improvement of the electroactive surface area, while according to electrochemical impedance spectroscopy (EIS), the charge transfer resistance decreased from 95.7 Ω to 19.7 Ω after CN modification. Results showed that the modified CN/Ni-F cathode, achieved a 15 times improvement of H2 O2 accumulation, which represented 13.8 times higher current efficiency (CE) for H2 O2 generation via two-electron oxygen reduction. Its H2 O2 generation ability was comparable to other carbonaceous cathodes like graphite and carbon cloth. Furthermore, CN/Ni-F also enhanced the electrocatalytic reduction of Fe 3+ . Regarding STZ degradation by EF, the apparent kinetic rate constant ( k app = 1.15 × 10 −2 min −1 ) was 5.22 times higher than the kinetic rate constant obtained with the unmodified Ni-F cathode ( k app = 2.2 × 10 −3 min −1 ), thus confirming the superiority of CN/Ni-F electrode. In addition, a possible STZ degradation pathway was proposed according to the intermediates identified during EF (aromatic by-products and inorganic ions (SO4 2−, NH4 + and NO3 − )). Finally, 5 cycles experiments showed that the CN/Ni-F cathode had a good stability in terms of H2 O2 accumulation and STZ degradation.